Design comparison of ordinary concentric brace frames and special concentric brace frames for seismic lateral force resistance for low rise buildings - Grusenmeyer, Eric (Kansas State University, 2012)
Braced frames are a common seismic lateral force resisting system used in steel structures. Ordinary concentric braced frames (OCBFs) and special concentric braced frames (SCBFs) are two major types of frames. Brace layouts vary for both OCBFs and SCBFs. This report examines the inverted-V brace layout which is one common arrangement. OCBFs are designed to remain in the elastic range during the design extreme seismic event. As a result, OCBFs have relatively few special requirements for design. SCBFs are designed to enter the inelastic range during the design extreme seismic event while remaining elastic during minor earthquakes and in resisting wind loads. To achieve this, SCBFs must meet a variety of stringent design and detailing requirements to ensure robust seismic performance characterized by high levels of ductility. The design of steel seismic force resisting systems must comply with the requirements of the American Institute of Steel Construction’s (AISC) Seismic Provisions for Structural Steel Buildings. Seismic loads are determined in accordance with the American Society of Engineers Minimum Design Loads for Buildings and Other Structures. Seismic loads are very difficult to predict as is the behavior of structures during a large seismic event. However, a properly designed and detailed steel structure can safely withstand the effects of an earthquake. This report examines a two-story office building in a region of moderately high seismic activity. The building is designed using OCBFs and SCBFs. This report presents the designs of both systems including the calculation of loads, the design of frame members, and the design and detailing of the connections. The purpose of this report is to examine the differences in design and detailing for the two braced frame systems.
Keywords: Ordinary Concentric Brace Frame; Special Concentric Brace Frame; Seismic Lateral Force Resisting Systems; Architectural engineering (0462); Civil Engineering (0543)